Fed transparency and policy expectation errors: A text analysis approach - Eric Fischer; Rebecca McCaughrin; Saketh Prazad; Mark Vandergon (Federal Reserve Bank of New York, 2023)
This paper seeks to estimate the extent to which market-implied policy expectations could be improved with further information disclosure from the FOMC. Using text analysis methods based on large language models, we show that if FOMC meeting materials with five-year lagged release dates-like meeting transcripts and Tealbooks-were accessible to the public in real time, market policy expectations could substantially improve forecasting accuracy. Most of this improvement occurs during easing cycles. For instance, at the six-month forecasting horizon, the market could have predicted as much as 125 basis points of additional easing during the 2001 and 2008 recessions, equivalent to a 40-50 percent reduction in mean squared error. This potential forecasting improvement appears to be related to incomplete information about the Fed's reaction function, particularly with respect to financial stability concerns in 2008. In contrast, having enhanced access to meeting materials would not have improved the market's policy rate forecasting during tightening cycles.
Keywords: E43; E52; E58; C80; 330; interest rates; monetary policy; central bank and policy; sentiment analysis